Spectroscopic investigations on the binding of an iodinated chlorin p6-copper complex to human serum albumin. Issue 12 (31st October 2017) - Sarbadhikary, P.; Dube, A.
Abstract : An iodinated chlorin p 6 copper complex showed high affinity to bind human serum albumin, the binding site was predicted and it was demonstrated that binding did not affect protein conformation. Abstract : The insertion of suitable metals or high Z elements in tumour-avid tetrapyrrole compounds is a promising approach to obtain potential agents for multimodal cancer therapeutics and tumour imaging. Using chlorin p 6, a chlorophyll derivative, we synthesized a novel iodinated chlorin p 6 -copper complex (IC p 6 -Cu) that can be applied to the photodynamic therapy and photon activation therapy of cancer. In the present study, we investigated the interaction of IC p 6 -Cu with human serum albumin (HSA) using UV-Vis absorption and fluorescence spectroscopy. The addition of HSA to IC p 6 -Cu at physiological pH led to a ∼7 nm red shift in its Soret and Q band absorption. The binding constant ( K b ) and the number of binding sites ( n ) of IC p 6 -Cu obtained from the quenching of the intrinsic fluorescence of HSA were 2.9 × 10 6 M −1 and 1.2 respectively. The distance between the Trp-214 residue and IC p 6 -Cu computed from Förster non-radiative energy transfer (FRET) theory was 3.1 nm. The emission of the IC p 6 -Cu fluorescence when excited at the protein's Trp absorption (295 nm) further substantiated the FRET between the Trp residue and IC p 6 -Cu. Synchronous spectroscopy revealed that the quenching of protein Trp fluorescence was higher than that of Tyr with no significant shift in peak position. Results suggested that HSA acts as a carrier protein for IC p 6 -Cu with a high probability that the binding of IC p 6 -Cu occurred at subdomain IIA and the binding had no effect on the conformation of HSA.